Improving the mathematical formulation for the detailed scheduling of refined products pipelines by accounting for flow rate dependent pumping costs - Cafaro, Vanina (2013)
This work presents a continuous-time mixed-integer linear programming (MILP) formulation to find the best detailed schedule for single-source multi-product pipelines, minimizing the total operating costs. By knowing the aggregate plan including pumping and delivery tasks, the best detailed solution tends to minimize pump stoppage/restart costs as well as pumping energy charges associated to the head loss inside the pipeline, which are strongly dependent on the flow rate at every pipeline segment. Pumping costs for transporting products into the pipeline are estimated by introducing a novel piecewise linear calculation of the energy loss. The proposed approach is applied to find the optimal detailed schedule for a real-world case study consisting of a single source pipeline with multiple offtake stations. Important reductions in the operational costs with regards to previous contributions are obtained.